Optimalisasi Pelayanan Data Pada Website Badan Pusat Statistik Provinsi Sumatera Selatan - Trio Wira Dharma; Hasmawati (Politeknik Piksi Ganesha Indonesia, 2022)
This study aims to produce a strategy for optimizing data services on the BPS website of South Sumatra Province. Key informants in this study include the Head of BPS South Sumatra Province, Functional Position Groups, and the Community as users. Statistical descriptive analysis technique. The results of the research on BPS data services for the Province of South Sumatra show that the availability of data on the website can be accounted for and is by statutory regulations. The provision of data services through the website is by the conditions and capabilities of service providers and recipients while adhering to the principles of efficiency and effectiveness according to user needs. The determination of public service standards has involved community participation. The absence of discrimination, namely not discriminating against ethnicity, race, religion, class, gender, and economic status of people who use data services. Routinely conduct customer satisfaction surveys to improve data services. However, the community itself has the right to file a complaint if the data service at the BPS for the Province of South Sumatra is not satisfactory through the whistle-blowing system